Regulasi Penyiaran dalam Wacana Glokalisasi pada Viralitas Berita Jalan Rusak Lampung - Dwi Ayu Setiowati; Chairunisa (LPPM Universitas HKBP Nommensen, 2025)
The development of digital communication technology has fundamentally changed the global broadcasting system, which was previously linear and territorial, into an interactive and cross-border communication space. The viral phenomenon of news about damaged roads in Lampung is a case study that illustrates how local issues can penetrate the global space through digital network mechanisms. This study aims to analyze the transformation of the broadcasting system in the digital era using the Media Convergence theory (Jenkins, 2006) and the Geo-Cybernetic paradigm (Puspitasari, 2022) as theoretical frameworks. Convergence theory explains how old and new media interact within the digital communication ecosystem, while the geo-cybernetic approach highlights the interconnectedness between geographical and cybernetic spaces in the global circulation of information. The method used was descriptive qualitative with a literature study approach, which included analysis of Law Number 32 of 2002 concerning Broadcasting, academic articles, and online media data related to the virality of Lampung news. The results of the study show that the digital broadcasting system works adaptively and decentralistically, where social media algorithms create a feedback loop mechanism that expands the reach of information without institutional control. This shows that broadcasting regulations in Indonesia are still limited to frequency-based broadcasting, so they are not yet able to accommodate the dynamics of global digital communication. Thus, a new regulatory paradigm is needed that integrates algorithmic ethics, digital literacy, and participatory governance within a geo-cybernetic framework.